Raising sons or daughters for old age? Influence of children's gender on intergenerational family support in rural families - Jiguang, Zhu; Yuncan, Wang; Yunxing, Song (Frontiers in Public Health, 2023)
Based on an empirical analysis of panel data covering four periods of the China Family Tracking Survey, this research examines the influence of children’s gender on parents' economic situation and life care. The results show that in rural areas, sons mainly provide economic support, while daughters mainly provide life care, thus forming a gender-based division of labour. With increasing off-farm job opportunities for daughters, they provide more economic support for their parents, but the time they spend on housework for their parents is reduced. As the number of children in a family has increased, daughters’ role in supporting their parents has decreased. This research shows that although the traditional son-centred pension mode in China has not completely disintegrated, it has changed significantly. The findings reveal that changes in family size and improvements in women's status are important factors in changing family support patterns.